46 - CONSIDERATIONS ABOUT THE SCIENTIFIC PRODUCTION ON HOME ASSISTANCE AND DEPENDENT ELDERLY: A LITERATURE REVIEW (Fiep Bulletin - online, 2011)
The human ageing is an individual or collective process resulting from biological changes, psychological and social. This reality is a consequence of decrease of birth and mortality indicators determining increase in incidence of chronic degenerative diseases-, which can lead to deficits functional, and consequently the dependency of the elderly. Many elderly addicted to remain at home with the support of Eldery's caretaker and professionals to guide the assistance. Thus, study aims to analyze current trends publications and studies developed on the relationship between the dependent elderly and home assistance. Developed a descriptive study literature review type by lifting the bibliographic databases electronic of BIREME, data from the title through publications theoretical relationship between health sciences descriptors (DECS) " dependent elderly " and "home assistance" and a history which included studies published in the period 2005-2009. Found 48 studies, 46 in MEDLINE and 02 LILACS. Most was published in the year 2006 (35,42%), followed by 2005 (27,08%) and 2008 (18,75%). At the publications, 50% had approach qualitative; 60,42% were published in English and 97,92% were publications in periodically (journals and magazines). The more thematic studies were addressed in Nursing assistance to elderly suffering for some pathology (37,14%); eldery's caretaker and elderly dependents living in domicile (14,28%); short-term targeted common problems with care for the elderly at home (11.43%). Like this it is evident that ageing is a significant issue today, and only recently, there was an increase of literature, because there are a number considerable publications on the subject, fact perceived traversing the two descriptors "home assistance" and "dependent elderly". It is expected that this review is a tool that subsidie discussions, help in disseminating this knowledge and have applicability in daily practice of health care professional.
Keywords: home assistance; dependent elderly; nursing